Quality Management of Educational Service (Case Study of Academic Service on Sambas 1 State Senior high School (SMAN 1 Sambas)) - Lisa Yuniza; Sukmawati Sukmawati; Muhammad Chiar (STKIP Singkawang, 2019)
This study aims to identify and analyze the form of quality management education services at SMAN 1 Sambas. This study applies a qualitative approach that uses descriptive methods. The process of analyzing data through four stages were data collection, data reduction, data presentation, and conclusion. Based on the research that has been done, the following results are obtained. (1) The quality planning of education services carried out in SMAN 1 Sambas involves various parties so that they reflect and hope that they want; (2) The implementation of the quality of educational services carried out in SMAN 1 Sambas involves the school in finding solutions to overcome the problems that occur; (3) Quality control of educational services carried out at SMAN 1 Sambas is carried out through the division of teaching tasks and follow-up on evaluation results; (4) Follow-up on the quality of education services carried out in SMAN 1 Sambas through evaluation of school programs and analysis of evaluation of learning outcomes and (5) Supporting factors and barriers to the quality of educational services in SMAN 1 Sambas based on existing facilities and infrastructure in school. Therefore, it can be concluded that the quality management of education services at SMAN 1 Sambas is running well.